Dampak Nasionalisme Konsumen Terhadap Niat Beli Produk dalam Negeri - Al Annur Pramdipta Ramaddan; Amrita Gita Saraswati Devi; Amilia Windy Trihapsari; Dayinta Ahna Diwasasri; Aulia Inggar Nabila; Ayesa Farhana (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
Using a systematic literature review approach to various previously published studies, this research investigates the influence of consumer nationalism on the intention to purchase domestic products. The purpose of this study is to find patterns of results, influencing components, and the impact of consumer nationalism on their behavior when purchasing local products. Data were collected from articles in relevant national and international journals, particularly those discussing ideas about consumer nationalism, consumer ethnocentrism, and factors determining purchase intention. The findings of the study indicate that consumer nationalism has a positive and significant effect on consumers' intention to purchase domestic goods. A number of variables, including product quality perceptions, price sensitivity, cosmopolitanism levels, and consumer demographics, especially Generation Z, who tend to be involved in the digital world, influence this effect. In addition, this study found that customer awareness, attitudes, and preferences towards local products are influenced by social media and digital campaigns such as the Bangga Buatan Indonesia (Proudly Made in Indonesia) program. The results of this study provide strategic benefits for businesses when they develop marketing plans based on the value of nationalism. These results can also be used as a reference for public policies aimed at increasing consumption and competitiveness of domestic products through the implementation of such policies.